Population Ageing and Pension Reform in a Small Open Economy with Non-Traded Goods - Leon Bettendorf; Ben Heijdra (Tinbergen Institute, 2005)
In this paper we study the implications of population ageing in an economy with a sizeable non-traded goods sector. To this effect a highly stylized micro-founded macro model is constructed in which the age structure of the population plays a non-trivial role. The model distinguishes separate birth and death probabilities (thus allowing for net population change), allows for age-dependent labour productivity (thus mimicing life-cycle saving), and includes a rudimentary pension system (thus allowing for intergenerational redistribution). The model is used to analytically study demographic and pension shocks.
Keywords: D91; E13; F41; H55; 330; fertility rate; overlapping generations; pension reform; demographic shocks; non-traded goods; Rentenreform; Fertilität; Schock; Overlapping Generations; Alternde Bevölkerung; Altersstruktur der Bevölkerung